Evaluation of drought tolerance in various petunia genotypes based on their morpho-physiological and biochemical responses - Cheheltanan, Leyla; Khosravi, Saeed; Shoor, Mahmoud; Tehranifar, Ali; Nemati, Hossein (Ornamental Horticulture, 2025)
Due to water resource constraints, studying and selecting drought-tolerant ornamental plants, along with a better understanding of their physiological and biochemical mechanisms, can help enhance their productivity in arid and semi-arid environments. A factorial experiment based on a completely randomized design was conducted with three water regimes (no stress – 90% container capacity (CC), moderate stress – 60% CC, and severe stress – 30% CC) in eight petunia genotypes, namely: Heirloom petunia (P1), Petunia × hybrida Supercascade White (P2), Petunia × hybrida grandiflora Frost Blue (P3), Petunia × hybrida grandiflora crimson star (P4), Petunia milliflora Picobella Rose Morn (P5), Petunia grandiflora Tritunia White (P6), Petunia grandiflora Success 360 Blue (P7), and Petunia Supercascade Red (P8). After the application period of the water regimes, morphophysiological, biochemical, and growth variables were evaluated over a total experimental duration of 120 days. Photosynthetic pigments and growth parameters were reduced under stress conditions in all Petunia genotypes. Under drought conditions, P1 and P5 genotypes exhibited higher performance, production of osmotically active solutes and activities of antioxidant enzymes, lower electrolyte leakage, and smaller reduction of relative water content than the other genotypes. Catalase and superoxide dismutase had no major antioxidative functions in P8 genotype and was recognized as the most vulnerable to severe water stress. These findings highlight the superior drought tolerance of genotype P1, followed by P5, indicating their potential for cultivation in water-limited environments. This provides valuable insights for breeding programs and landscaping applications in drought-prone areas.